Los capítulos de inversiones en la Alianza del Pacífico, el CPTPP y el T-MEC: convergencia sustantiva, divergencia procesal - Toro-Fernandez, Juan-Felipe (2021)
This article compares the investment chapters of the Additional Protocol to the Framework Agreement of the Pacific Alliance (PA-AP), the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) and the United States-Mexico-Canada Agreement (USMCA). Our objective is to determine their degree of normative convergence. We conclude that these investment chapters include very similar substantive rules and principles on international investments in terms of definitions, the rules’ scope of application, treatment standards (national treatment and most favored nation treatment), absolute standards (international minimum standard of treatment, fair and equitable treatment, and full protection and security), investment protection rules (direct and indirect expropriation, compensation, and transfers), and performance requirements. We also conclude that these investment chapters differ, in some respects very strongly, regarding investor-State dispute settlement (ISDS). First, TPP and USMCA rules are often similar and frequently diverge from PA-AP rules. Second, party coverage and protection coverage diverge strongly between the USMCA vis-a-vis the PA-AP and CPTPP. Thus, as a consequence of substantive convergence and strong procedural divergence, we argue that complainants will most likely choose the forum between the PA-AP, CPTPP and USMCA according to procedural reasons.